Microwave-Assisted Extraction of Gymnemic Acid: A Potent Antidiabetic Agent from Gymnema sylvestre R.B. and its Comparison with Conventional Extraction Technique - Pednekar, S.; Joshi, N.; Menon, S.; Khairnar, B. (Asian Journal of Chemistry, 2011)
Microwave assisted extraction and liquid-liquid extraction have been investigated to determine the content of gymnemic acid from leaves of Gymnema sylvestre R.Br. The extraction of gymnemic acid is commercially very important because it is a potent antidiabetic agent and used in various pharmaceutical products. The effect of single factors such as microwave power, microwave irradiation time, extraction solvent volume, sample size, etc. are evaluated and standardized. Microwave assisted extraction and liquid-liquid extraction has been comparatively evaluated for their efficiency to extract the content of gymnemic acid from leaves of Gymnema sylvestre. The extracts obtained by various extraction techniques were analyzed for the content of gymnemic acid by validated RP-HPLC method. Deacylgymnemic acid was used a reference standard and the amount of gymnemic acid was calculated by using molecular weight correction factor. Taking into account the extraction yield, extraction time, solvent and cost of extraction, better results were obtained by microwave assisted extraction (50 % methanol 5 min at 20 % power with minimum sample size). By applying microwave assisted extraction the use of organic solvents was minimized. Toxicity and comparative bioavailabilty of the microwave assisted extraction extract were also evaluated on animal model.